Study of heritability, genetic advance and variability for yield contributing characters in rice - Bisne, Rita; Sarawgi, AK; Verulkar, SB (Bangladesh Journal of Agricultural Research, 2010)
The knowledge of genetic variability in a given crop species for characters under improvement is important in any plant breeding programme. Heritability with genetic advance are more helpful in predicting the gain under effective selection. Genetic parameters for yield and its correspondent characters in rice were estimated from a trial with four CMS lines, eight testers and thirty-two hybrids evaluated for thirteen characters related to yield. Low, moderate, and high genotypic and phenotypic coefficient of variations were observed. High genotypic and phenotypic coefficient of variations were expressed by harvest index, total number of filled spikelets per panicle, 100-grain weight and spikelet fertility percentage. High heritability coupled with high genetic advance was exhibited by harvest index, total number of chaffy spikelets per panicle, grain yield per plant, total number of filled spikelets per panicle and spikelet fertility percentage and selection may be effective for these characters. Key Words: Heritability; variability; genetic advance in rice. DOI: 10.3329/bjar.v34i2.5788 Bangladesh J. Agril. Res. 34(2) : 175-179, June 2009